Exploring Drug Addicts’ Relapse Triggers: Sample from United Arab Emirates - Aljasmi, Alyaa; Alhorani , Mohamed; Algarbawi, Fatima (Al-Adab Journal, 2024)
Relapse into substance use after completing detoxification and rehabilitation treatment is a worldwide public, social, and health concern. In general, the relapse rate for substance use disorder patients is 40 to 60 percent. Although substance use remains a burden in the UAE, very little is known about relapse among substance use disorder (SUD) patients. Therefore, this study aims to examine the triggers associated with relapse to substance use at one of the treatment centers. This study is essential to implement an integrated intervention to address relapse in various stages of recovery, from accepting the patient to their reintegration into the community.The methodology of the current qualitative study is based on in-depth interviews with 30 SUD patients at Treatment Center, simultaneously achieving two methodological goals: tracking the addiction process from leaving the center to navigating the surrounding environment, involving family, friends, and work, and identifying the unique experiences of the respondents.The studies produced several findings: The study explores therapeutic, social, and personal triggers, including exposure to the drug after quitting, self-desire, and readiness to use after interacting with these triggers. First, the therapeutic triggers (receiving, internal treatment, therapeutic programs, integration plan with society, etc.) serve as a main trigger for relapse. The second category is social triggers, which are elements of the outside world that can lead, such as exposure to drugs, family, friends, and the workplace. In addition to the personal reasons for relapse includes "the powerlessness to exercise self-control, negativity from both the addict and others around them, considering drug trafficking as a means of generating income, linking drug use to happiness, depression, pain, and loneliness, and not accepting life without drugs."The study recommends developing and improving the existing motivational and therapeutic programs to address relapse, enabling fundamental changes in the therapeutic phase and social integration. Additionally, inclusion plans should be enhanced to address the recovered individuals' needs for community reintegration. Future studies are also recommended to evaluate the effectiveness of existing relapse prevention programs and adjust prevention plans and strategies.